ICRC AND ITS SHIPS: LEGAL STATUS, IMMUNITIES AND PRIVILEGES FROM THE PERSPECTIVE OF INTERNATIONAL LAW - Enny Narwati; Dina Sunyowati; Lina Hastuti; Nilam Andalia Kurniasari (Fakultas Hukum Universitas Trisakti, 2019)
This paper analyses the legal status of two matters from the perspective of International Law which are the International Committee of the Red Cross (ICRC) and the ships’ used by the organization by employing qualitative methods through interview with some key personnel of the ICRC Indonesia and the Indonesian Navy. This study shows that the ICRC is not a public inter-governmental organization and cannot be deemed as one. However, ICRC is a subject of International Law thus, this give the organization international legal personality and immunity. Regarding the legal status of the ships used by the organization to carry out its duty, this paper conclude that they are considered as private vessels. Therefore, they do not possess immunity and privileges bestowed by International Law. Nevertheless, they are protected by International Law. Keywords: ICRC, International Legal Personality, Legal Status, Privileges and Immunities, Status of Ships